A Study on Nutraceuticals - Bajaj, Manya (International Journal of Nutrition, 2024)
Hippocrates trusted foodstuff, maybe medicine, and healthcare management, administration, and costing are important. Nutraceuticals, derived from "nutrition" and "pharmaceutical," cover differing healing areas like “antagonistic-hard, cold and cough, sleep difficulties, digestion, cancer prevention, osteoporosis, blood pressure, cholesterol management, pain relievers, depression, and diabetes”. “Stephen De Felice”, “founder of the Foundation for Innovation in Medicine, created the term in 1989”.Functional foods, like milk and orange juice, supply health benefits that surpass food, in the way that a better lifestyle and a lower risk of ailment. Nutraceuticals, in another way, involve fortified dairy products like milk that help avoid or cure illnesses and disorders apart from anaemia.Conventional arrangements like Solvents extraction , Soxhlet distillation ,maceration and “Non conventional designs” like ‘Microwave assisted origin’, Ultrasound Assisted Extraction are used to restore the bioactive material from plants for nutraceuticals.”The Indian Health and Dietary Supplement Association” supports drug, nutraceutical, herbaceous, and direct selling energies by categorising them based on chemical arrangement, food type, and conventional arrangement.This paper gives a brief review on nutraceuticals ,its history , its market trend , extraction techniques , benefits and its applications .
Keywords: nutraceuticals; extraction; allergy; anticancer; diabetes